2018
DOI: 10.1186/s12913-018-2991-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists’ views of implementing a stratified treatment approach for patients with low back pain in Germany: a qualitative study

Abstract: BackgroundThe STarT-Back-Approach (STarT: Subgroups for Targeted Treatment) was developed in the UK and has demonstrated clinical and cost effectiveness. Based on the results of a brief questionnaire, patients with low back pain are stratified into three treatment groups. Since the organisation of physiotherapy differs between Germany and the UK, the aim of this study is to explore German physiotherapists’ views and perceptions about implementing the STarT-Back-Approach.MethodsThree two-hour think-tank worksho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(99 citation statements)
references
References 53 publications
2
96
0
1
Order By: Relevance
“…Primary users of the SBT are physiotherapists and primary care physicians [2, 3, 10]. In addition, utilisation of the tool by health insurance companies might have the potential for a more targeted disbursement of resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary users of the SBT are physiotherapists and primary care physicians [2, 3, 10]. In addition, utilisation of the tool by health insurance companies might have the potential for a more targeted disbursement of resources.…”
Section: Discussionmentioning
confidence: 99%
“…Back pain is one of the most prevalent symptoms encountered in primary care [1]. Its treatment is challenging for primary care practitioners, such as physiotherapists or general practitioners [2, 3]. It has been discussed that determining the prognosis of back pain is a priority for research and practice and may have the potential to supersede diagnosis in its relevance [4].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of qualitative studies by Synnott et al (2015) found that although physiotherapists recognised psychosocial factors in LBP patients, they preferred to treat the mechanical aspects of LBP and may stigmatise people based on psychosocial factors. Furthermore, physiotherapists often indicated they lacked the training and skillset to effectively address psychosocial factors in clinical practice (Karstens et al, 2018;Synnott et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This has the potential to also affect a patient's choices for treatment practitioner. Concern about lack of financial incentives to adopt stratified care for LBP was identified in a qualitative study of German physiotherapists (Karstens et al, 2018), which also reported participants felt they did not have the necessary skills to deliver psychosocially informed treatment. Given these challenges, it is likely that the adoption of a stratified model of care for LBP requires an approach tailored to each country to ensure it is fit for purpose and acceptable to multiple stakeholders (Sowden et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since previous qualitative research has called attention for potential barriers that may prevent the successful implementation of the STarT Back in the UK as well as in other countries [2427], the SPLIT research team has introduced several adjustments to the original model since its early conception. For example, rheumatologists and PTs from the research team delivered a training program, which was tailored to each professional group.…”
Section: Introductionmentioning
confidence: 99%